THE IMPORTANCE OF REGIONAL ORGANIZATIONS ESTABLISHED IN EURASIA FOR TURKEY: SHANGHAI COOPERATION ORGANIZATION - Aksu, Zehra (Fırat Üniversitesi, 2023)
In this study, the SCO-Turkey relations are analyzed; An answer has been sought to what are the reasons that make the SCO important for Turkey. Founded in 1996 with the Shanghai Five, the SCO was officially established on June 15, 2001. The organization has nine full members, three observer members, and nine dialogue partners. Turkey is one of the important countries with “dialogue partner status” among SCO partners. Turkey, which joined the organization as a dialogue partner at the 2012 Beijing Summit, wants to improve its relations with Eurasian countries and strengthen its position vis-à-vis Western countries with its model country mission. The gradual shift of the world's economic and financial centre to the East and the search for alternatives to the EU membership make the SCO important for Turkey. Turkey's problem of trust in Western states, whose EU membership process is in a deadlock, leads Turkey to establish relations with the SCO and to follow a proactive foreign policy. It is expected that Turkey will carry its dialogue partnership status at the SCO to observer state status in the coming years to remind that Turkey has a strategic value against Western states. Full membership status is not expected due to the reality that Turkey cannot give up its cooperation with Western institutions and organizations for many years.

ŞİÖ-Türkiye ilişkilerinin analiz edildiği bu çalışmada; ŞİÖ’yü Türkiye açısından önemli kılan sebeplerin neler olduğu sorusuna cevap aranmıştır. 15 Haziran 2001 yılında resmi olarak kurulan ŞİÖ dokuz tam üye, üç gözlemci üye ve dokuz diyalog ortağına sahiptir. Türkiye, ŞİÖ ortakları içerisinde “diyalog ortağı statüsü”ne sahip önemli ülkelerden biridir. 2012 Pekin Zirvesi’nde örgüte diyalog ortağı olarak katılan Türkiye, model ülke misyonu ile Avrasya ülkeleriyle olan ilişkilerini geliştirmek ve Batılı ülkeler karşısındaki konumunu ise güçlendirmek istemektedir. Dünyanın ekonomik ve finansal merkezinin giderek Doğu’ya kayması ve AB’ye üyeliğin gerçekleşmemesine alternatif arayışları ŞİÖ’yü Türkiye açısından önemli kılmaktadır. AB’ye üyelik süreci açmaza giren Türkiye’nin Batılı devletlere olan güven sorunu Türkiye’yi ŞİÖ ile ilişkiler kurmaya ve proaktif bir dış politika izlemeye yönlendirmektedir. Türkiye’nin Batılı devletler karşısında stratejik bir değer olduğunu hatırlatacak bir hamle olarak ŞİÖ’de sahip olduğu diyalog ortaklığı statüsünü önümüzdeki yıllarda gözlemci devlet statüsüne taşıyacağı beklenmektedir. Türkiye’nin uzun yıllardır Batılı kurum ve kuruluşlarla geliştirmiş olduğu işbirliklerinden vazgeçemeyeceği realitesi nedeniyle tam üyelik statüsü beklenmemektedir.
Avrasya’da Kurulan Bölgesel Örgütlerin Türkiye Açısından Önemi: Şanghay İşbirliği Örgütü